Familial dementia with Lewy bodies with VPS13C mutations. (December 2020) - Kobayashi, Ryota; Naruse, Hiroya; Koyama, Shingo; Kawakatsu, Shinobu; Hayashi, Hiroshi; Ishiura, Hiroyuki; Mitsui, Jun; Ohta, Yasuyuki; Toda, Tatsushi; Tsuji, Shoji; Otani, Koichi
Highlights: VPS13C mutations associate with early-onset autosomal recessive PD. Novel pathogenic variants in VPS13C were identified in two siblings with DLB. Two siblings exhibited a phenotype of DLB without obvious parkinsonism. The clinical spectrum of patients with VPS13C variants could be wider than expected.